PROCEDURES AND STRATEGIES IN THE VIETNAMESE-ENGLISH TRANSLATION OF CULTURE-SPECIFIC ITEMS - Ngô, Thị Huyền (2020)
Translation of cultural words has proved itself to be important in the context of Vietnam‟s integration into the world. The issue poses quite a few challenges for the students and translators though. The study sought to investigate common problems among students when translating culture-specific items and strategies to solve the problems in the light of Newmark‟s theory on translation procedures. The book Wandering through Vietnamese culture and its author Huu Ngoc were chosen for major data collection and affirmation for research findings. At the same time, 30 questionnaire responses from 30 surveyed students provided statistics to find out their difficulties and strategies to deal with the terms. It was discovered that 60% of the students encounter culture-specific terms on a regular basis and their most serious problems were the achievement of naturalness in the target language, lack of cultural knowledge in the source language and their provision of various translations for only one source language word. Analysis of document data, previously collected and divided into ecology, material culture and customs-traditions, revealed that couplets with transference and description was the most-employed solution by Huu Ngoc, though description could be in various forms. Interview with the author indicated important considerations in cultural translation: accuracy, conciseness and the ability to trigger the source language‟s ideas of the translated versions. The importance of understanding the cultural nuance of one culture-specific items rather than its lexical meaning was emphasized. The study was expected to support those interested in the research topic and especially ULIS students in their translation training. However, further research should be carried out on the connotative equivalence in the translation of culture-specific items and equivalence at above-word level